Spiritual Care at the End of Life - Dunne, Tad (The Hastings Center report, 2001)
Dying patients have more than medical needs. In fact, what they feel most sharply, whether or not they are religious, are spiritual concerns. The Christian theological virtues of faith, hope, and charity, properly interpreted and translated to reflect the universal concerns with which they are connected, provide a starting point.